High rate of macrolide resistance and closely genetically related Mycobacterium abscessus complex strains identified among both cystic fibrosis and non-cystic fibrosis patients within two countries - Dohál, Matúš; Dvořáková, Věra; Hromádková, Michaela; Pinková, Martina; Amlerová, Jana; Schwarz, Marek; Spitaleri, Andrea; di Marco, Federico; Hnilicová, Jarmila; Gondáš, Eduard; Rasmussen, Michael E; Porvazník, Igor; et al. (Microbiology spectrum, 2024)
UNLABELLED: Mycobacterium abscessus is an emerging opportunistic pathogen affecting patients with chronic lung diseases, primarily cystic fibrosis (CF), or those under immunosuppression. Hence, investigations into the epidemiology and transmission of M. abscessus and accurate antibiotic susceptibility data are essential for the effective treatment of infections caused by this pathogen. This retrospective nationwide study included all clinical M. abscessus isolates (n = 59) from 29 patients diagnosed in the Czech Republic and Slovakia between 2018 and 2023. Whole genome sequencing (WGS) was performed to identify clusters and classify isolates into predominant circulating clones (DCC). Subspecies identification of unique isolates showed subspecies abscessus as the most prevalent (69.0%). The results of drug-susceptibility testing showed that 65.5% of all isolates were resistant to at least three antibiotics tested. CF patients under 24 years of age were the most at-risk group for M. abscessus infection. WGS identified seven clusters (including two cross-border) comprising CF and non-CF patients with a total clustering rate of 48.3%. One cluster involved patients infected with subspecies massiliense strains differing by 0 single nucleotide polymorphisms hospitalized in the same center. Furthermore, we identified representatives of all major DCCs. This study revealed predominant Mycobacterium abscessus complex clones circulating in the Czech Republic and Slovakia. The results show the high discriminatory power of WGS in the molecular epidemiology of M. abscessus and provide supporting evidence of direct or indirect cross-transmission of subspecies massiliense among both CF and non-CF patients. IMPORTANCE: This study highlights the importance of understanding Mycobacterium abscessus transmission because it poses a growing threat to vulnerable populations, especially young cystic fibrosis patients. Investigating how it spreads and which antibiotics work best is crucial for effective treatment. This research used whole genome sequencing to track M. abscessus and found evidence of potential transmission between patients, including across borders. The findings suggest that dominant strains are circulating and some patients may be infected through direct or indirect contact. This knowledge can inform infection control and treatment strategies.
Keywords: resistance; epidemiology; non-tuberculous mycobacteria; transmission; M. abscessus; DCC